REAKSI INVESTOR DALAM PASAR MODAL TERHADAP PERPPU ORMAS (Peraturan Pemerintah Pengganti Undang-Undang Organisasi Masyarakat) NO 2 TAHUN 2017 (Event Study Pada Perusahaan yang Terdaftar Dalam LQ45 di Bursa Efek Indonesia) - Eka Sriwulan Sari; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe aim of the study was to prove empirically the differences betweenabnormal return and trading volume activity before and after the validity ofperppu ormas. The study utilized a quantitative designer involving the dataobtained from secondary sources such as Yahoo Finance. The populationconsisted of 45 companies listed in the Indonesia stock exchange LQ45. Thesamples were determined by using purposive sampling with a criteria of thoselisted in the LQ45 during the period of August 2017-January 2018 and wheneverthe data required were accessible. 45 companies that met the criteria were usedas sample of the study. The analysis was done by using paired sample t-testsupported by software SPSS for windows.The results of the study indicated that there is not significant differencebetween the abnormal return dan trading volume activity before and after thevalidity of perppu ormasKey word : abnormal return, trading volume activity